Producción y análisis del uso de glutatión en aplicaciones cosméticas (2024)
Currently, there is a growing need to protect the environment due to serious problems arising from pollution. In response, various mitigation strategies have been developed, generating high demand for products obtained through biotechnology. This discipline leverages natural resources sustainably, offering more environmentally friendly alternatives and generating lower greenhouse gas emissions, such as carbon dioxide, compared to traditional methods. This has been applied in various industries to generate more environmentally friendly raw materials, moving away from traditional methods like chemical synthesis and avoiding technified crops, which, to meet the high demand for products, are very extensive, displacing native biodiversity; in the cosmetic industry, this new trend has gained considerable strength. For this reason, this research focuses on developing a microparticle that is part of a potential cosmetic formulation for skin care, using a functional cosmetic ingredient like glutathione, which will be stabilized in a nanometric or micrometric size capsule. The objective is to obtain microparticles to perform encapsulation optimization tests, where the microparticle's loading capacity, morphological characteristics, and antioxidant activity will be evaluated through in vitro and in vivo tests, if possible in cell cultures. The expectation is to obtain a microparticle containing glutathione that is stable and highly antioxidant, which can be incorporated into a possible cosmetic matrix for skin care.